Women’s attitude towards representation of women domestication in advertisement - Endah Siswati (Masyarakat, Kebudayaan dan Politik, 2019)
The persuasive strategies in advertising often use gender-biased signs or languages, which represent women’s subordination and domestication. On the other hand, the construction and development of individual gender concepts begin in childhood through the parents, peer groups, schools and mass media socialisation, including advertisements. Thus, how women, who act as wives and mothers, view and respond to female domestication will influence how they socialise gender concepts towards their children. This study examines how the mother of the student at Laboratory Primary School, Malang, view and address the representation of female domestication advertisements in  Nova and Nyata tabloids. This qualitative research was conducted in Malang City and using self-researcher as the primary research instrument. Data was collected through Focus Group Discussion (FGD) and interview; then the data were analysed by qualitative analysis method of Miles & Huberman. This study found that the subjects viewed the tendency of using female models in advertising is reasonable and not a problem as long as fulfil specific criteria. The representation of women’s domestication in the domestic sector in the advertisement is also considered reasonable because the representation is the nature of women and self-reflection of women themselves. However, the subjects disagree if the description of women is only as mother who were responsible for household chores. In addition, about the representation of women’s domestication in the public sector in advertisements, the subjects stated that they agree if the ads depict the success of men in the public, however, the ads should also describe the involvement and success of women in the public sector and not only describe women as servants.